The tyranny of fascination : an exegesis presented in partial fulfillment of the requirements for the degree of Master of Fine Arts at Massey University, Wellington, New Zealand - Davidson, Emily Maria (Massey University, 2012)
In this exegesis I will discuss the photographic works that I have constructed during my research into the photograph as a reproducible object, I will also be discussing the ability that photographic reproducibility has to unlimber assigned or received meaning whilst also questioning and mediating the assigned meaning of the original artefact that it depicts. This questioning happens in part because of the ability that the photograph has to stand in for the object that it is derived from; and in part because of the ability that the re-produced photograph has to speak with comparable authority to the original photograph. I believe that the reproducibility of the photograph allows the photographic object to move out into the world allowing an image to presented in many places simultaneiously, and that this allows it’s meaning to be contested intertextually in as much as the image is able to exist plurally, to interact with many different scenarios, to be used for many different functions, and to exist in scenarios which an original or unique object could not. For the sake of simplicity and brevity I often use the terms photographic, photography and camera in this essay; When I use the term photographic, I intend it to mean any form of photographic production, this could be a traditional black and white photograph, or it could be a silkscreen print, I am not attempting to categorise or classify these things. My intent with this is to be inclusive of technologies, methods, and images – not exclusive. The photograph, as I use the term herein can be taken to mean ‘an image which is produced photographically’ – In this I am speaking to images that are photographic objects, unless noted I am not speaking to a particular photograph.
Keywords: Emily Maria Davidson; Artistic photography; Criticism and interpretation; Philosophy